Traumatic Spinal Injuries in Northern Finland - Niemi-Nikkola, Ville; Saijets, Nelli; Ylipoussu, Henriikka; Kinnunen, Pietari; Pesälä, Juha; Mäkelä, Pirkka; Alen, Markku; Kallinen, Mauri; Vainionpää, Aki (Spine (Philadelphia, Pa. 1976), 2018)
A retrospective epidemiological study. To reveal incidence and epidemiological features of traumatic spinal injuries (TSI) in Northern Finland. In Finland the annual incidence of traumatic spine fractures requiring inpatient care has been found to be 27/100,000, while international incidences have varied across the range of 16-64/100,000. More specific epidemiological data from Finland is not available. Internationally, the most common mechanisms of injury are road traffic as well as low and high falls. Associated injuries occur in 30% to 55% of cases. The study sample included patients with traumatic spinal injury admitted to Oulu University Hospital (OYS) with injury between the January 1, 2007 and December 31, 2011. Patient information was collected from the hospital care register, including all inpatient and outpatient visits and surgical procedures. Traumatic spinal column and spinal cord injuries were identified using International Classification of Diseases 10th revision or Nordic Classification of Surgical Procedures codes and all patient records were manually reviewed. Nine hundred seventy-one patients met the criteria for TSI. The mean annual incidence of hospitalized traumatic spinal injuries was 26/100,000 in the whole of Northern Finland and 35/100,000 in the OYS main responsibility area. The most frequent etiology of TSI was low falls, which accounted for 35.8% of the injuries, followed by road traffic and high falls. Lumbar spine was the most common site of the fracture. Spinal surgery was performed in 376 (38.7%) cases. Three hundred eight patients (31.7%) suffered from associated injuries, 101 (10.4%) had a spinal cord injury, and 71 (7.3%) a brain injury. Low falls in elderly and road traffic injuries in younger age groups were the most common etiology of traumatic spinal injuries in Northern Finland and should be given more attention in primary prevention. 3.